2016
DOI: 10.1016/j.foodhyd.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of limited enzymatic hydrolysis on structure and emulsifying properties of rice glutelin

Abstract: 27The influence of the degree of hydrolysis (DH) on the structure, solubility, 28 rheology, and emulsifying properties of rice glutelin was investigated. Structural 29 properties were characterized using analysis of molecular weight distribution, surface 30 hydrophobicity, intrinsic fluorescence, and Circular Dichroism (CD) spectra. Protein 31 hydrolysis changed molecular weight, increased flexibility, altered surface 32 hydrophobicity, and increased solubility. Oil-in-water emulsions were prepared from 33 ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(95 citation statements)
references
References 54 publications
10
74
0
Order By: Relevance
“…31 In addition, during the analysis of the secondary structure, -sheets as protein structure ("trains") are relatively stable, whereas the -helix, -turn and random coils are relatively flexible and open. 16 In Table 1, enzymatic hydrolysis decreased the -sheet regions and increased the -helix, -turn and random coil regions, indicating that the secondary structure in the protein attains a more flexible and extended form after enzyme treatment. 32 These changes in surface hydrophobicity and secondary structure in the protein showed that the protein hydrolysates had more flexible structures than the native protein.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…31 In addition, during the analysis of the secondary structure, -sheets as protein structure ("trains") are relatively stable, whereas the -helix, -turn and random coils are relatively flexible and open. 16 In Table 1, enzymatic hydrolysis decreased the -sheet regions and increased the -helix, -turn and random coil regions, indicating that the secondary structure in the protein attains a more flexible and extended form after enzyme treatment. 32 These changes in surface hydrophobicity and secondary structure in the protein showed that the protein hydrolysates had more flexible structures than the native protein.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the surface hydrophobicity index began to decrease with a higher DH, which might be a result of the decrease in peptide size in hydrolysates affecting the affinity of the ANS probe toward the protein . In addition, during the analysis of the secondary structure, β ‐sheets as protein structure (“trains”) are relatively stable, whereas the α ‐helix, β ‐turn and random coils are relatively flexible and open . In Table , enzymatic hydrolysis decreased the β ‐sheet regions and increased the α ‐helix, β ‐turn and random coil regions, indicating that the secondary structure in the protein attains a more flexible and extended form after enzyme treatment .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence measurements were performed using a fluorescence spectrophotometer (F‐7000, Hitachi, Japan) according to the method of Xu et al . A quartz cell with 1 cm path length was used for intrinsic fluorescence measurements.…”
Section: Methodsmentioning
confidence: 99%